2023
DOI: 10.3390/fermentation9030272
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Sweet Sorghum (Sorghum bicolor L. Moench) Using Immobilized Yeast (Saccharomyces cerevisiae) Entrapped in Calcium Alginate Beads

Abstract: As the population grows, there is a need to address the continuous depletion of non-renewable energy sources and their negative effects on the environment. This led to a substantial assessment of possible innovations and raw materials to increase the volumetric productivity of alternative fuels to supply the energy needed worldwide. In addition to its environment-friendly properties, a biofuel derived from plant-based sources is also a sustainable material. For high ethanol production from plant-based biofuel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Numerous studies on these biomass sources have been explored to find out their potential as renewable sources. Some of these are sweet sorghum juice as a potential raw material for alcohol production [ 17 ] and peanut shell and cornick industry wastewater as raw materials for briquette production [ 18 ]. Optimization studies on these biomass sources have also been explored [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on these biomass sources have been explored to find out their potential as renewable sources. Some of these are sweet sorghum juice as a potential raw material for alcohol production [ 17 ] and peanut shell and cornick industry wastewater as raw materials for briquette production [ 18 ]. Optimization studies on these biomass sources have also been explored [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zong et al 5 prepared glucoamylase microcapsules using the water/oil/water (W/O/W) complex coacervation freeze-drying method. The solid-state sustained-release results showed that the glucoamylase microcapsules could slowly release in the solid state for over 336 h. Cadiz et al 6 used sodium alginate to immobilize yeast and found that immobilized yeast has a longer action time. The earlier research proves that immobilization technology can endow enzymes with slow-release properties and effectively extend the action time of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…prepared glucoamylase microcapsules using the water/oil/water (W/O/W) complex coacervation freeze‐drying method. The solid‐state sustained‐release results showed that the glucoamylase microcapsules could slowly release in the solid state for over 336 h. Cadiz et al 6 . used sodium alginate to immobilize yeast and found that immobilized yeast has a longer action time.…”
Section: Introductionmentioning
confidence: 99%